Guided Learning To Improve Self Directed Learning: A Study Among First Year Psychology Students In Unimas - Ida Juliana, Hutasuhut; Mohamad Azhari, Abu Bakar; Kartini, Abdul Ghani (Centre for Applied Learning and Multimedia, UNIMAS, 2020)
Many studies agreed that students in higher education institution, particularly in year one, still rely on teacher-centred learning (Du Toit-Brits, 2019). This phenomenon was also found, particularly among first year UNIMAS students. They tend to wait for lecturers to spoon-feed them as what they had experienced during their secondary education. In industrial revolution 4.0 where knowledge is everywhere, learning is much easier. However, learning depends on the students themselves. University students should sufficiently equip themselves with the learning skills which prepared them to be more independent and self-directed in their learning.